Novel energy-efficient designs of vertical-cavity surface emitting lasers for the next generations of photonic systems. (1st August 2022) - Tian, Si-Cong; Ahamed, Mansoor; Larisch, Gunter; Bimberg, Dieter
Abstract: High-speed vertical-cavity surface-emitting lasers (VCSELs) at different wavelengths present the backbone of high-speed optical links showing large bandwidth density. The state of the art of present designs of VCSELs is summarized, including driving conditions. Several novel approaches for the design of GaAs-based VCSELs and VCSEL arrays are reported, potentially leading, e.g. to lower power consumption, much larger single mode output and larger bandwidth. The first one is based on using the photon lifetime as a system sensitive optimization parameter. The second one reports for the first time details of a disruptively novel (patented) design based on oxidizing the apertures from multiple etched holes in varying arrangements and finally on multi-aperture designs in one device. These designs are essential for improving the energy-efficiency of modules by optimizing the interplay of electronic driver and photonic device.